Investment effect in influencing the economic surrounding based on countries income level / Azlan Shah Ali - Ali, Azlan Shah (2012)
Investment is one of the important models in stabilizing and influencing the economic growth. Investment effect may vary across countries based on the policy and economic condition of a country. Total Investment that divided mainly into Foreign Direct Investment (FDI) and Direct Domestic Investment (DDI) will be used as dependant variable to test it relationship and effect toward economic surrounding such as Inflation, Tax and Unemployment rate. This study will be based on panel data on 42 countries that are mainly from developing countries. The countries will then be divided into four different level of income that will showed the relationship on FDI inflow and DDI towards Inflation, Unemployment and Tax revenue from 1970 to 2010. The result indicates different impact and consequences of different economic surrounding towards FDI inflow and DDI. Besides that, the relationship in investment itself between FDI inflow and DDI will also be examined based on the Granger Causality effect.